2018
DOI: 10.1155/2018/9030185
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Subclinical Hypothyroidism in Acute Coronary Syndrome in Nondiabetics: Detailed Analysis from Consecutive 1100 Patients from Eastern India

Abstract: Background The association between subclinical thyroid dysfunction (defined by no symptoms or clinical features of hypothyroidism but biochemically TSH level in the range of above 5 miu/ml but below 10 miu/ml with normal FT4 level) and Acute Coronary Syndrome (ACS) is not known so far. This study was done to calculate the prevalence of subclinical thyroid dysfunction in patients with ACS. Methods A retrospective chart review of 1100 consecutive patients was done who presented to Emergency Department with sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 11 publications
5
6
1
Order By: Relevance
“…In contrast to those findings and to the present ones, a recent study of heart failure patients found that LVEF did not differ between those with SCH and those who were euthyroid [18]. Moreover, the LVEF did not differ by thyroid fraction among individuals with acute coronary syndrome in another report [34].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to those findings and to the present ones, a recent study of heart failure patients found that LVEF did not differ between those with SCH and those who were euthyroid [18]. Moreover, the LVEF did not differ by thyroid fraction among individuals with acute coronary syndrome in another report [34].…”
Section: Discussioncontrasting
confidence: 99%
“…This is important, as screening that focuses on vulnerable population is likely to detect disease more frequently and timely intervention will reduce the chances of overt disease. 17 Prevalence in females was double as compared to males in the present study, which is in corroboration to findings of other studies. 5,17,18 Subclinical hypothyroidism has numerous complications on female fertility, maternal and fetal outcomes in pregnancy.…”
Section: Discussionsupporting
confidence: 93%
“…17 Prevalence in females was double as compared to males in the present study, which is in corroboration to findings of other studies. 5,17,18 Subclinical hypothyroidism has numerous complications on female fertility, maternal and fetal outcomes in pregnancy. It has been cited in many studies that incidence of subclinical hypothyroidism escalates with advancing age.…”
Section: Discussionsupporting
confidence: 93%
“… 14 These consequences are very important for the onset of ACS where parts of myocardium functionality is impaired due to ischaemia related injury. 15 Since all cardiovascular abnormalities are reversed restoration of euthyroidism (“subclinical hypothyroidism”) should be the goal. The clinical features of hyperthyroidism can be blunted by using beta adrenergic or drugs like neo mercazole.…”
Section: Clinical Impact Of Alterations In Thyroid Functionmentioning
confidence: 99%
“… Helmy et al. 15 2016 Prospective ACS 300 At admission 1 year Prevalence of subclinical hypothyroidism is 5% in ACS patients. Lymvaios et al.…”
Section: The Prognostic Value Of Thyroid Dysfunction In Acsmentioning
confidence: 99%